Zygotic development without functional mitotic centrosomes. - Megraw, T.L.; Kao, L.R.; Kaufman, T.C. (Current Biology, 2001)
The centrosome is the dominant microtubule-organizing center in animal cells. At the onset of mitosis, each cell normally has two centrosomes that lie on opposite sides of the nucleus. Centrosomes nucleate the growth of microtubules and orchestrate the efficient assembly of the mitotic spindle. Recent studies in vivo and in vitro have shown that the spindle can form even in the absence of centrosomes and demonstrate that individual cells can divide without this organelle. However, since centrosomes are involved in multiple processes in vivo, including polarized cell divisions, which are an essential developmental mechanism for producing differentiated cell types, it remains to be shown whether or not a complete organism can develop without centrosomes. Here we show that in Drosophila a centrosomin (cnn) null mutant, which fails to assemble fully functional mitotic centrosomes and has few or no detectable astral microtubules, can develop into an adult fly. These results challenge long-held assumptions that the centrosome and the astral microtubules emanating from it are essential for development and are required specifically for spindle orientation during asymmetric cell divisions.